Penerapan Prinsip-prinsip Etika Bisnis dalam Transaksi E-Commerce : Membangun Kepercayaan Konsumen - Olipian Resky Pernando; Wanda Berliandes; Ela Juliyani (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
This research aims to analyze the application of business ethics principles in e-commerce transactions in building consumer trust. The method used in this research is Systematic Literature Review (SLR), which involves collecting 30 articles sourced from Google School from 2019-2024, which focus on the application of business ethics principles in e-commerce transactions in building consumer trust. The research results recommend that the application of these principles can build consumer trust. The findings of this study emphasize the importance of business ethics principles in e-commerce transactions in building consumer trust, especially in an era of very rapid technological development.